Investigation of composite electrolytes with structured silica materials for lithium ion batteries - Sann, Kerstin; Justus Liebig University Giessen (My University, 2016)
Composite electrolytes, consisting of an organic lithium electrolyte with dispersed filler material therein, were experimentally studied concerning their electrochemical behavior. The influence of added filler material (isolating particles) on a liquid lithium electrolyte, especially boundary layer phenomena, the influence of surface charge, viscosity trends and electrochemical stability were evaluated. Hence, different types of silica filler material, mesoporous and surface designed silica as well as commercially available silica, were systematically deployed with a range of pore geometry, pore size and specific surface area. The crucial role of the chemical composition of the filler surface exposed to an electrolyte of 1 M lithium hexafluorophosphate (LiPF 6 ) in a solvent mixture of ethylene carbonate (EC) and diethylene carbonate (DEC) at the ratio 3:7 was investigated.Besides different measurements (conductivity, zeta potential, viscosity, electrochemical window) and material variations, some formal considerations were done like the calculation of the conductivity decrease with volume exclusion assumptions and estimation of activation energies for the movement of the ions in solution or the number of possible adsorption sites on the silica surfaces.These formal considerations were only helpful to a certain extent. The conductivities varied much between the systems and therefore, they differed more or less from the theoretical volume exclusion assumptions. The characteristics of the calculated activation energies could hardly be linked with the measured conductivities. Most of the dispersions had the same activation energy as the pure electrolyte, when taking measurement deviations into account. The calculation of silica surface sites showed, that the number density of ions in the used 1 M electrolyte is one order of magnitude higher than the number density of possible adsorption positions on the silica surfaces in the dispersions.The conductivity decreased with addition of silica filler material but varied considerably for the different fillers. Due to the sedimentation of the silica, stirring was necessary whereby no particulate network was formed. Several materials showed deviations from the the conductivity trend expected from calculation of volume exclusion. Hence, boundary layer effects or interaction of electrolyte ions with the silica surface (filler material) are assumed. Accordingly, zeta potential measurements showed partially trapping of Li + ions on the silica surface dependent on the surface functionalization and therefore the surface charge. As the Li + ions are the essential charge carrier in lithium electrolytes this adsorption reaction is unfavorable.Viscosity studies showed mainly Newtonian behavior of the composite dispersions with a liquid organic electrolyte, which again proves that no attractive particle network was formed. However, the mechanical properties of the electrolytes changed significantly in some systems with the amount of filler material, with only little change of the conductivity.Determination of the electrochemical window showed a slight widening for one system, maybe due to special morphology of the silica material Cab-O-Sil in this work, whereby most of the dispersions exhibited the same electro-chemical window as the pure electrolyte.Within all the measurements and results no clear trend for the behavior and characteristics of silica filler materials in a liquid lithium electrolyte could be observed. The conductivities varied between the composite electrolytes, but showed a conductivity decrease, which was stronger than the expected decrease with volume exclusion assumptions. With the used silica materials no particle network was formed, but different influences depending on the characteristics of the silica materials could be observed. Hence, one can conclude that the surface chemistry and morphology of the silica filler materials influence the electrochemical behavior of liquid lithium electrolytes, which can be positive as well as negative. Improvement of good liquid lithium electrolytes with addition of silica as filler material did only lead to marginal changes in this work.

Komposit-Elektrolyte, bestehend aus einem organischen lithiumhaltigen Elektrolyten mit verschiedenen darin dispergierten Silica-Materialien (Füllmaterial), wurden in dieser Arbeit hinsichtlich ihres elektrochemischen Verhaltens experimentell untersucht (vgl. Bild 0.2). Dabei war der Einfluss der hinzugefügten Silica-Materialien auf den flüssigen Lithium-Elektrolyten, bestehend aus 1 M Lithiumhexafluorophosphat (LiPF 6 ) in einem Lösemittelgemisch aus Ethylencarbonat (EC) und Diethylencarbonat (DEC) in einem Mischungsverhältnis von 3:7, von Interesse. Vor allem Leitfähigkeiten, Grenzflächen-Phänomene, Einfluss von Oberflächenladungen, Viskositätsverhalten und die elektrochemische Stabilität wurden untersucht. Dafür wurden systematisch unterschiedliche Silica-Materialien eingesetzt, sowohl mesoporöse und oberflächenmodifizierte Silica, als auch kommerziell erhältliche Silica-Materialien, mit verschiedenen Porengeometrien, Porengrößen und spezifischen Oberflächen.Innerhalb der durchgeführten Messungen und theoretischen Berechnungen konnte kein eindeutiger Trend für das Verhalten von Silica-Materialien dispergiert in einen flüssigen Lithium-Elektrolyten festgestellt werden. Die Leitfähigkeiten variierten zwischen den verschiedenen Elektrolyt-Systemen, wobei die Zugabe der Silica-Materialien zu einer Leitfähigkeitsabnahme geführt hat, die teilweise stärker war, als durch Berechnung des Volumenausschlusses angenommen. Mit den verwendeten Silica-Materialien wurde kein partikuläres Netzwerk erhalten, jedoch konnten verschiedene Einflüsse, abhängig von den Charakteristiken der zugesetzten Silica, beobachtet werden.Zusammenfassend kann gesagt werden, dass die Oberflächenchemie und Morphologie der Silica-Materialien das elektrochemische Verhalten eines flüssigen lithiumhaltigen Elektrolyten sowohl positiv als auch negativ beeinflussen können. Insgesamt hat die Zugabe der Silica-Materialien nur zu geringen Änderungen der Eigenschaften des flüssigen Elektrolyten geführt. Die Verbesserung eines gut leitenden flüssigen Lithium-Elektrolyten durch Zugabe von Silica-Materialien erscheint damit wenig möglich.
Keywords: Lithium-Ionen-Batterie; disperse Elektrolyte; Silica-Material; Leitfähigkeit; lithium ion battery; disperse electrolytes; silica material; conductivity; ddc:540